A novel conceptual design method for aviation PMSG based on thermal modeling - Wang He; Ai Fengming; He Linke; Zhou Zhongzheng; Wang Yangang (International Journal for Simulation and Multidisciplinary Design Optimization)
A multi-disciplinary optimization design method for permanent magnet synchronous generators based on thermal modeling is proposed in this paper. The complex coupling among the thermal, electromagnetic, and mechanical systems and the difficulties in optimization with conflicting objectives of multiple disciplines has been studied. Firstly, a multi-disciplinary design optimization model is established based on the coupling relationships between the thermal, electromagnetic, and mechanical performance of permanent magnet synchronous generators. Then, optimization objectives are set as low temperature-rise, low volume and weight, and sizeable electromagnetic size. The critical parameters in the thermal, electromagnetic, and mechanical systems of the generators are considered decision variables. The particle swarm optimization algorithm is selected as a multi-objective problem-solving algorithm to support the multi-disciplinary optimization of thermal motor design. Based on thermal modeling, a high disciplinary coupling and high physical fidelity concept design method for aerospace permanent magnet synchronous generators is presented. This conceptual design method can effectively reduce the design cost of aerospace generators, shorten the development cycle, and promote the design and development of aerospace permanent magnet generators.